Нецукровий діабет: сучасні аспекти клініки, діагностики та лікування - Кравчун, Н. О. (Clinical Endocrinology and Endocrine Surgery, 2011)
Problems of pathogenesis, clinics, diagnostics, differential diagnostics and treatment of diabetes insipidus are reported.